Bimetallic MOF (Mn/Co) constructed by active dicyandiamide linker for a promising combustion catalyst of solid propellant - Mingcheng Ge; Xian Xu; Ze Su; Ye Zhong; Binfang Yuan; Huisheng Huang; Jianguo Zhang; Zhimin Li (Defence Technology)
Combustion catalyst is a key modifier for the performance of composite solid propellant. To exploit high-efficiency combustion catalyst, a fascinating bimetallic metal-organic framework [MnCo(EIM)2(DCA)2]n (1) was constructed by an active dicyandiamide (DCA) linker, Mn2+, Co2+ centers, and an 1-ethylimidazole (EIM) ligand. 1 possesses good thermal stability (Tp = 205 °C), high energy density (Eg = 24.34 kJ/g, Ev = 35.93 kJ/cm3), and insensitivity to impact and frictional stimulus. The catalytic effects of 1 contrasted to monometallic coordination compounds Mn(EIM)4(DCA)2 (2) and Co(EIM)4(DCA)2 (3) on the thermal decomposition of AP/RDX composite were investigated by a DSC method. The decomposition peak temperatures of AP and RDX of the composite decreased to 335.8 °C and 206.4 °C, respectively, and the corresponding activation energy decreased by 27.3% and 43.6%, respectively, which are better than the performances of monometallic complexes 2 and 3. The gas products in the whole thermal decomposition stage of the sample were measured by TG-MS and TG-IR, and the catalytic mechanism of 1 to AP/RDX was further analyzed. This work reveal potential application of bimetallic MOFs in the composite solid propellants.